2003
DOI: 10.1530/eje.0.1490137
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of congenital adrenal hyperplasia in Slovenian patients: a novel Ala15Thr mutation and Pro30Leu within a larger gene conversion associated with a severe form of the disease

Abstract: Objective: To analyse the mutational spectrum, the associated haplotypes and the genotype -phenotype correlation, and to design a reliable and rational approach for CYP21 mutation detection in Slovenian congenital adrenal hyperplasia (CAH) patients. Design: Molecular analysis of the CYP21 gene was performed in 36 CAH patients and 79 family members. Methods: Southern blotting, sequence-specific PCR amplification (PCR-SSP), sequence-specific oligonucleotide hybridisation (PCR-SSO) and sequencing were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 34 publications
4
32
1
Order By: Relevance
“…This phenotypic variability of Ile172Asn mutation has also been reported in other European populations showing an otherwise good correlation between the genotype and phenotype (3,10,19,20). Similarly, many investigators have reported phenotypes more severe than expected in carriers of the Pro30Leu mutation (9,10,15,18,21). The finding of the Pro30Leu mutation linked to a gene conversion in the promoter region or with an additional mutation, Ala15Thr, could explain the increased severity of phenotypes in Slovenian patients (18).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This phenotypic variability of Ile172Asn mutation has also been reported in other European populations showing an otherwise good correlation between the genotype and phenotype (3,10,19,20). Similarly, many investigators have reported phenotypes more severe than expected in carriers of the Pro30Leu mutation (9,10,15,18,21). The finding of the Pro30Leu mutation linked to a gene conversion in the promoter region or with an additional mutation, Ala15Thr, could explain the increased severity of phenotypes in Slovenian patients (18).…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, many investigators have reported phenotypes more severe than expected in carriers of the Pro30Leu mutation (9,10,15,18,21). The finding of the Pro30Leu mutation linked to a gene conversion in the promoter region or with an additional mutation, Ala15Thr, could explain the increased severity of phenotypes in Slovenian patients (18). The in vitro expression analysis did not demonstrate the impairment of enzyme activity by Ala15Thr mutation alone (22) but it is not excluded that this mutation has a synergistic effect on 21-hydroxylase activity when combined with the Pro30Leu mutation and/or gene conversion in the promoter region (23).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The results of molecular analyses of 24 out of 28 patients were previously reported. 6,15 Legend: The step that can be augmented by extraadrenal hydoxylation via hepatic cytochrome P450 CYP2C19 is bolded. CYP11A1 -cholesterol side-chain cleavage enzyme; CYP17 -17-alpha-hydroxylase / 17,20-lyase; HSD3B2 -3β-hydroxysteroid dehydrogenase; CYP21A2 -steroid 21-hydroxylase; CYP11B1-steroid 11-β-hydroxylase; CYP11B2 -aldosterone synthase; 17β-HSD -17-beta-hydroxysteroid dehydrogenase.…”
Section: Molecular Analysis Of Cyp21a2 Genementioning
confidence: 99%